Activity-based allocation and optimization for carbon footprint and cost in product lifecycle. (1st November 2019) - Gui, Fangzhi; Ren, Shedong; Zhao, Yanwei; Zhou, Jianqiang; Xie, Zhiwei; Xu, Chen; Zhu, Fen
Abstract: Low-carbon design is a sustainable method, which coordinates the carbon footprint, cost and performance of each stage in product lifecycle from the design source to satisfying low-carbon demand. It is also a significant technology to reduce the carbon emission before manufacturing. To effectively and efficiently reduce the carbon emission, a low carbon-oriented design method is studied in product lifecycle. A product is modularized to function units for obtaining carbon footprint, which are quantified based on the framework of PAS2050. In order to identify the high-emission parts, an activity-based method is used to allocate the carbon footprint. Through the lifecycle analysis, the major parts and components characterized with high carbon emission are picked out according to allocation result. Due to the close relationship and conflict between the carbon emission and cost of product, an improved genetic algorithm with a novel selection mechanism, which used the correlation function, is presented to optimize these parts in order to reduce both the carbon footprint and cost. In the end of the paper, a vacuum pump is taken as a case to verify the allocation method and the improved genetic algorithm, and the result shows the effective reduction of carbon footprint and cost.